2022
DOI: 10.1038/s41598-022-16717-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic implications of rim restriction following glioma surgery

Abstract: Rim restriction surrounding the resection cavity of glioma is often seen on immediate post-op diffusion-weighted imaging (DWI). The etiology and clinical impact of rim restriction are unknown. We evaluated the incidence, risk factors and clinical consequences of this finding. We evaluated patients that underwent surgery for low-grade glioma (LGG) and glioblastoma (GBM) without stroke on post-operative imaging. Analyses encompassed pre- and postoperative clinical, radiological, intraoperative monitoring, surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…A recent study by Strand et al also found a higher risk for peri-tumoral strokes in the temporal lobes, yet they included both rim-pattern and sector shaped DWI restrictions in their definition of strokes 8 . Our study focused only on wedge-shaped ischemic lesions, while minimal or rim-pattern DWI changes in the periphery of the resection cavity, often defined as post-operative restrictive changes, were not considered as ischemic strokes 18 . We perform most of our surgical resections trans-cortically, yet our assumption is that even mild retraction, often required in temporal and insular tumors, might be enough to induce ischemia in diseased brain parenchyma, especially in recurrent or previously irradiated cases.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Strand et al also found a higher risk for peri-tumoral strokes in the temporal lobes, yet they included both rim-pattern and sector shaped DWI restrictions in their definition of strokes 8 . Our study focused only on wedge-shaped ischemic lesions, while minimal or rim-pattern DWI changes in the periphery of the resection cavity, often defined as post-operative restrictive changes, were not considered as ischemic strokes 18 . We perform most of our surgical resections trans-cortically, yet our assumption is that even mild retraction, often required in temporal and insular tumors, might be enough to induce ischemia in diseased brain parenchyma, especially in recurrent or previously irradiated cases.…”
Section: Discussionmentioning
confidence: 99%